Management Of Anxiety When Facing Exams at SMP Negeri 1 Juwiring - Ima Nia Uliasari; Ella Putri Febria; Maya Desvira Riandy; Septiani Hapidah (BADAN PENERBIT STIEPARI PRESS, 2023)
Education as one of the fields that plays an important role in improving the progress of the nation. In order for the education and learning process to run effectively, management is needed in educational units starting from elementary to secondary education, which is school-based management. The process of forming exam anxiety can be described by the presence of a stimulus in the form of an image of a potential threat or danger that appears just before the exam. Triggers of anxiety before exams are influenced by irrational thoughts, for example not being able to answer exam questions, getting grades below school competency standards, answer sheets not being scanned by a computer and not believing in one's own abilities. According to Soetartawi, the trigger for anxiety before exams is irrational thinking in students so that it gives a negative response to students. Research shows that 80% of success is determined by emotional factors, while intellectual factors only play a role of 20%. The main problem with emotional barriers in facing exams is a lack of self-confidence. As soon as you enter the exam room, you suddenly feel like going back, anxious, nervous, too cautious and afraid of being wrong. This makes students think that all questions look difficult. School exams are one of the requirements for grade promotion and graduation for students. Handling the level of anxiety before exams can help students increase their confidence in their abilities and prevent students from failing when taking school exams. The method of this service is carried out by means of lectures which are attended by class 9A from SMP N 1 Juwiring. The result of this dedication is obtained in the form of an informant's understanding related to how to overcome anxiety or anxiety management when individuals experience anxiety.